On some fučík type problem with cubic nonlinearity ADI Approach to the Particle Diffusion Problem in Magnetic Fluids - Polevikov, V.; Tobiska, L. (Mathematical Modelling and Analysis, 2011)
The present study is devoted to the development of an ADI approach to simulate two-dimensional time-dependent diffusion process of ferromagnetic particles in magnetic fluids. Specific features of the problem are the Neumann boundary conditions. We construct an ADI scheme of formally second order accuracy approximation in time and space. It is proved that the scheme is absolutely stable and it has the accuracy in the energy norm of the second order in time and the order 3/2 in space. The numerical results of a test problem indicate that the convergence rate in space is of the second order as well.